The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5194/aab-55-567-2012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters by Bayesian inference for dual purpose Jaffarabadi buffaloes

Abstract: Knowledge of genetic parameters is essential for improved reproductive management and increased yield. Quantitative analysis of genetic parameters is lacking for many breeds of buffaloes. This article provides the first estimate of genetic parameters for dual purpose (meat and milk) Brazilian Jaffarabadi buffaloes, using Bayesian inference. Data on milk yield (MY), lactation length (LL), weight at 205 days (W205) and 365 (W365) days of age, and average daily gain (ADG) from 205 to 365 days of age were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Similar findings were obtained in different studies (Thiruvenkadan et al, 2009;Kul et al, 2017;Erdogan et al, 2021;Kaplan, 2021;Alkoyak and Öz, 2022). BW values (175.41 ± 2.06 kg) were found to be higher than the results of earlier research (Thiruvenkadan et al, 2009;Akhtar et al, 2012;Şekerden, 2014;Pandya et al, 2015;Kul et al, 2017;Yılmaz et al, 2017;Erdogan et al, 2021;Kaplan, 2021) for Murrah, Nili-Ravi, Surti, and Anatolian breeds, whereas higher values were reported by some studies (Shahin et al, 2010;Mendes Malhado et al, 2012;Vergara et al, 2012;Falleiro et al, 2013;Agudelo-Gómez et al, 2015;Shahjahan et al, 2017;El-den et al, 2020;Medrado et al, 2021). The least-square means for body measurements were similar to the results of literature (Uslu, 1965;Gürcan et al, 2011;Gavit et al, 2013;.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were obtained in different studies (Thiruvenkadan et al, 2009;Kul et al, 2017;Erdogan et al, 2021;Kaplan, 2021;Alkoyak and Öz, 2022). BW values (175.41 ± 2.06 kg) were found to be higher than the results of earlier research (Thiruvenkadan et al, 2009;Akhtar et al, 2012;Şekerden, 2014;Pandya et al, 2015;Kul et al, 2017;Yılmaz et al, 2017;Erdogan et al, 2021;Kaplan, 2021) for Murrah, Nili-Ravi, Surti, and Anatolian breeds, whereas higher values were reported by some studies (Shahin et al, 2010;Mendes Malhado et al, 2012;Vergara et al, 2012;Falleiro et al, 2013;Agudelo-Gómez et al, 2015;Shahjahan et al, 2017;El-den et al, 2020;Medrado et al, 2021). The least-square means for body measurements were similar to the results of literature (Uslu, 1965;Gürcan et al, 2011;Gavit et al, 2013;.…”
Section: Resultssupporting
confidence: 86%
“…The variance components and direct additive, maternal, and total heritabilities estimated for the studied traits are shown in Table 3. The direct additive heritability for BW was found to be consonant with Medrado et al (2021) and lower than the findings of Salces et al (2006), Mendes Malhado et al (2007, Shahin et al (2010), Akhtar et al (2012), Mendes Malhado et al (2012, Vergara et al (2012), Falleiro et al (2013), Salces et al (2013), Gupta et al (2015), Pandya et al (2015), El-den et al (2020), andKaplan (2021).…”
Section: Resultsmentioning
confidence: 74%
“…Estimates of genetic correlations between BWGW and WGW12 in buffaloes are also rare in the literature. The genetic correlations between body weights of buffaloes at various ages are moderate to high [19,24], presenting a behavior similar to that observed for BWGW and WGW12 for all the breeds studied here. Genetic correlations indicated that the selection for weight gains at younger ages leads to an increase in weight gains at 12 months, which allows producing more precocious buffalo animals.…”
Section: Discussionsupporting
confidence: 80%
“…However, similar estimates have been reported by Pareek and Narang (2014), Patil et al (2018) and Kumar et al (2022). In buffaloes, lower to higher heritability for milk yield have been reported by various researchers in different buffalo breeds (Aspilcueta-Borquis et al, 2010;Hossein-Zadeh, 2015;Malhado et al, 2012;Seno et al, 2010;Tonhati et al, 2008) which suggests there is sufficient additive genetic variation to respond to selective breeding.…”
Section: Discussionsupporting
confidence: 70%